Perbandingan Minat Belajar Peserta Didik Dengan Menggunakan Model Pembelajaran PAKEM Berbasis Fun Eksperimen dan Berbasis Video di Kelas IX MTs Madani Alauddin Pao - Pao Makassar. - Yusman, Yusman; Qaddafi, Muhammad; Ali, Ahmad (UIN Alauddin Makassar, 2025)
This study aims to compare the learning interest of students through the implementation of the PAKEM Learning Model Based on Fun Experiments and Video-Based in Class IX MTs Madani Alauddin Pao - Pao Makassar. This research is a quasi-experimental study with a Post-test-only Control Group Design. The population of this study was 191 students of Class IX MTs Madani Alauddin Pao - Pao Makassar who studied Science subjects, consisting of five classes. The research sample consisted of 66 individuals, namely Class IX D as experimental class 1 (PAKEM Based on Fun Experiments) and Class IX B as experimental class 2 (PAKEM Based on Video). The research instrument used was a learning interest test. The results of descriptive research show that the average value of learning interest of students taught using the PAKEM learning model Based on Fun Experiments is 52.35, while those taught with the PAKEM learning model Based on Video is 53.26. Considering the results of the 2-sample t-test hypothesis test, a sig. value of 0.018 was obtained with a t-count of 0.478 and a t-table of 2.02. Because sig. (0.018) <0.05 and t-count (0.478) <t-table (2.02), it is concluded that there is no significant difference in learning interest between students taught using the PAKEM learning model Based on Fun Experiments and Video Based in class IX MTs Madani Alauddin Pao - Pao Makassar